POSITIVE AND NEGATIVE EFFECTS OF ANTIBIOTICS - Yusupbekova, Xurshida; Zufarov, Fozil (INTERNATIONAL CONFERENCES, 2022)
Antibiotics are medicines that treat a bacterial infection by either killing the bacteria or preventing it from growing. It works for bacterial infections and sometimes protozoal infections, but is not effective enough for viral diseases. A person can take it orally or by injection. The revolution of antibiotics in medicine began in the 20th century, during a period when there was a significant decrease in the incidence. An antibiotic shortens the time period of a health problem, benefiting everyone involved in its production and consumption. Although it has eradicated several diseases, the widespread use of the drug and its easy availability have made microbes and bacteria resistant to it. In addition, some recent reports have drawn conclusions about mild and severe effects of antibiotics.